Research on Multi-Objective Operation Optimization of Integrated Energy System Based on Economic-Carbon Emission. Issue 1 (June 2020) - Wei, Mengju; Yang, Yang; Liu, Zhao; Wang, Yongli; Zhou, Minhan; Song, Fuhao
Abstract: The development of an integrated energy system (IES) is an important way to improve energy utilization, link renewable energy consumption and protect the environment. In this paper, physical modeling and analysis of the key equipment of IES, with economic costs and carbon emissions as the goal, established a multi-objective operation optimization model of the integrated energy system, and used particle swarm optimization to solve practical problems. Finally, taking a typical summer day as an example, the analysis illustrates the optimization results and verifies the feasibility of the model and algorithm.